Virtual reality? investment consultants’ claims about their own performance - Cookson, G; Jenkinson, T; Jones, H; Vicente Martinez, J (INFORMS, 2021)
Investment consultants market their services by claiming their fund manager recommendations add significant value. Using non-public data sourced from investment consultants and the UK regulator, we find no such evidence, but identify several practices that explain their exaggerated claims: comparisons to benchmarks instead of peers, inclusion of simulated and backfilled returns, use of investment horizons that allow losers to be forgotten, and unexplained exclusions of products from the analysis. Consultants do not fully disclose their methodology to investors, who therefore cannot verify or reliably compare their performance.